Real-time synchronization mechanizm for complex concurrently competing processes coordination - Banaszak, Zbigniew; Krogh, Bruce H. (Zielona Góra: Uniwersytet Zielonogórski)
This paper presents a new approach to automated development of control software for concurrency control of discrete event systems as well as to the synthesis of computer-aided tools for production real-time management. A new modelling technique for complex concurrently competing processes description is introduced, then, sufficient conditions for deadlocks avoidance are presented.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka